PENGARUH JOB STRESS, KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP TURNOVER INTENTION KARYAWAN HOTEL KAMANDALU UBUD - Sang Ayu Made Apriantini; I Gusti Ayu Imbayani; Pande Ketut Ribek (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2021)
The purpose of this study was to determine the effect of job stress, job satisfaction, and organizational commitment on turnover intention. This research was conducted at the Kamandalu Ubud hotel. This study uses multiple linear regression analysis to determine the effect of job stress, job satisfaction, and organizational commitment on employee turnover intention at Kamandalu Ubud hotel. Data were collected by distributing questionnaires and the sampling method used was saturated sampling. Testing the research hypothesis using SPSS 25.0 for Windows. The results showed that job stress had a positive and significant effect on turnover intention, meaning that the higher the level of job stress, the higher the level of turnover intention. Job satisfaction has a negative and significant effect on turnover intention, meaning that the higher the level of job satisfaction, the lower the turnover intention. Organizational commitment has a negative and significant effect on turnover intention, meaning that the higher the level of organizational commitment, the lower the turnover intention will be. In addition, job stress, job satisfaction and organizational commitment simultaneously have a significant effect on turnover intention. Based on the researcher's direct experience in this research process, there are several limitations that are experienced, namely: 1) the indicators used as descriptions of the variables under study can be added again so that the information obtained will be more detailed and diverse. 2) The questionnaire has not attached the length of time worked for each employee, so it is not able to identify how long the employee who became the respondent has worked at Hotel Kamandalu Ubud.